2011
DOI: 10.1258/acb.2010.010170
|View full text |Cite
|
Sign up to set email alerts
|

Consumptive hypothyroidism: a case report and review of the literature

Abstract: Hepatic haemangioendothelioma is a rare vascular tumour in infants and may be associated with a unique form of thyroid function abnormalities. Hepatic haemangioendotheliomata is capable of producing an excess of the thyroid hormone inactivating enzyme, type 3 iodothyronine deiodinase. The increased enzyme activity leads to rapid degradation of thyroid hormones, resulting in frank hypothyroidism. We report a case of a three-month-old neonate with multiple hepatic haemangioendotheliomata and associated hypothyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
1
23
0
1
Order By: Relevance
“…However, he required high doses of T4 to maintain euthyroid status during the early phase of the disease. This high dose requirement has been shown in previous cases, and some patients require combined T4 and T3 replacement or intravenous T3 replacement (10 ). However, the thyroid hormone requirement decreases with the involution of the tumor.…”
Section: Consumptive Hypothyroidismsupporting
confidence: 54%
“…However, he required high doses of T4 to maintain euthyroid status during the early phase of the disease. This high dose requirement has been shown in previous cases, and some patients require combined T4 and T3 replacement or intravenous T3 replacement (10 ). However, the thyroid hormone requirement decreases with the involution of the tumor.…”
Section: Consumptive Hypothyroidismsupporting
confidence: 54%
“…Congenital thyroid dysfunction may also arise in the context of other complex disorders, such as Alagille syndrome type 1 due to JAG1 mutations (ALGS1) [35] and hepatic or parotid massive hemangiomas, which may produce the thyroid hormone–inactivating enzyme type 3 iodothyronine deiodinase [36, 37]. …”
Section: Mild Hypothyroidism In Neonatesmentioning
confidence: 99%
“…Most studies on this type of consumptive hypothyroidism report the use of levothyroxine or levothyroxine plus liothyronine for treatment [1][2][3][4][5][6][7][8][9][10][11][12]14]; while 1 study reported the use of liothyronine plus prednisolone [13]. However, there is no report of using liothyronine plus propranolol for the treatment of consumptive hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%